Discovery and development of Factor Xa inhibitors (2015–2022) - Zheng, Wei; Dai, Xiaoqin; Xu, Binyao; Tian, Wei; Shi, Jianyou (Frontiers in Pharmacology, 2023)
As a pathological coagulation process, thrombus can lead to many serious diseases, including ischemic stroke, acute myocardial infarction (AMI), acute coronary syndrome (ACS), and deep venous thrombosis (DVT). And anticoagulant drugs are one of the most effective ways to prevent and treat these diseases. Although macromolecular anticoagulant drugs such as low molecular weight heparins (LMWHs) are widely used in the clinic, their characteristics of requiring injectable use hinder their further promotion in the clinic, and the disadvantages of oral anticoagulant drugs, such as warfarin and dabigatran etexilate, which can easily cause bleeding adverse effects, are also not addressed. FXa has gained attention because it lies at the intersection of the coagulation cascade pathways, whereas subsequently introduced FXa inhibitors such as rivaroxaban and apixaban, among others, have gained market popularity because of their high potency for anticoagulation and high specificity for FXa when administered orally. But some of the drawbacks that these FXa inhibitors have simultaneously such as fewer indications and the lack of an effective reversal drug when bleeding occurs are urgently addressed. The development of new FXa inhibitors therefore becomes one means of addressing these questions. This article summarizes the small molecule FXa inhibitors developed from 2015 to 2022, classifies them according to their scaffolds, focuses on the analysis of their structure-activity relationships, and provides a brief assessment of them.